Genetic Divergence and Biogeographic Patterns in the Deep-Sea Shrimp Plesionika semilaevis Across the Western Indian Ocean - S. Sreelakshmy; Shijin Ameri; Rekha Devi Chakraborty; P. Laxmilatha; Shubhadeep Ghosh (Thalassas: An International Journal of Marine Sciences, 2026)

A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Performance Evaluation of EOS-06 OCM-3 Chlorophyll-a Retrievals in Case-1 Waters - Chiranjivi Jayaram; Neethu Chacko; Rajdeep Roy; T. Devi Varaprasada Rao; P. V. Nagamani; T. V. S. Udaya Bhaskar; K. N. Babu; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Application of bioencapsulated microalgae in marine cladoceran (Penilia sp.) for enhancing growth and improve production of Asian seabass (Lates calcarifer) - K. Nanthini Devi; P. Santhanam; A. Shenbaga Devi; P. Raju; R. Sagaya Princy; K. Rajagopal; I. S. Bright Singh; A. S. Sahul Hameed; A. Jishnu Panamoly; P. Perumal (Journal of Applied Phycology, 2026)

Integrated profiling of drought tolerant rice landraces through comprehensive examination of gene expression, morpho-physiological traits, and biochemical responses during reproductive stage - P. Dharani; T. Nivethitha; S. Manju Devi; A. John Joel (Cereal Research Communications, 2026)

Unveiling the prevalence, pathogenic and molecular characterization of Xanthomonas strains responsible for bacterial leaf spot of tomato and pepper in India - P. Lokesh Babu; V. Devappa; J. Rajender; Neelam Geat; R. S. Devi; Rahul Patidar; Ainmisha Singh; V. K. Banarwal; Jasdeep Chatrath Padaria; Anju Kamra; Dinesh Singh (Journal of Plant Pathology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Unraveling genetic diversity in cowpea (Vigna unguiculata (L.) Walp.) for yield and yield attributing traits through multivariate analysis - S. Manju Devi; P. Jayamani (Vegetos, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Real-time earthquake magnitude estimation utilizing a mixed dataset set of observed and simulated P-wave onsets for the Kumaon Himalaya from Mw3.0–7.5 earthquakes - Suraj Kumar Pal; S. Devi; Sandeep; P. Kumar; A. Joshi; Monika; R. Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Fabrication of CoTe-phosphorus doped g-C3N4 photocatalytic engine: A leap towards eco-friendly hydrogen production - V. Bharathi Mohan; S. Jayachitra; P. Devi; P. Murugan; M. Sathish (Chemical Engineering Journal, 2025)

Production and Extraction of Red Bioactive Pigment from Streptomyces griseorubiginosus and Formulation of Bio-Lip Balm - S. Vignesh; P. M. Anandu; G. S. Gopuraj Varrier; Nikhil Brijmohan; G. Gokula Krishnan; Sanjeev K. Ganesh; Sreelakshmi R. Nair; V. Mohanasrinivasan; C. Subathra Devi (Indian Journal of Microbiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Unveiling the interaction, cytotoxicity and antibacterial potential of pyridine derivatives: an experimental and theoretical approach with bovine serum albumin - Rosalin Das; Patitapaban Mohanty; Pragyan P. Dash; Swagatika Mishra; Ajit K. Bishoyi; Lokanath Mishra; Laxmipriya Prusty; Devi P. Behera; Debasmita Dubey; Monalisa Mishra; Harekrushna Sahoo; Mohd S. Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spatiotemporal Changes of Pollutant Concentrations in South India during COVID-19 Lockdown Using Ground and Satellite-based data: a Comparative Analysis from the Machine Learning Model - Pelati Althaf; Nulu S. M. P. Latha Devi; Kanike Raghavendra Kumar (Water, Air, & Soil Pollution, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Innovative Approaches in Regulatory Affairs: Leveraging Artificial Intelligence and Machine Learning for Efficient Compliance and Decision-Making - C. S. Ajmal; Sravani Yerram; V. Abishek; V. P. Muhammed Nizam; Gayatri Aglave; Jayasri Devi Patnam; Rajeev Singh Raghuvanshi; Saurabh Srivastava (The AAPS Journal, 2025)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Harmony in nature's elixir: a comprehensive exploration of ethanol and nano-formulated extracts from Passiflora incarnata leaves: unveiling in vitro cytotoxicity, acute and sub-acute toxicity profiles in Swiss albino mice - Balasubramanian Deepika; Pemula Gowtham; Vijayashree Raghavan; Jane Betsy Isaac; Sobita Devi; Venkatakrishnan Kiran; Devadass Jessy Mercy; P. S. Sharon Sofini; A. Harini; Agnishwar Girigoswami; Koyeli Girigoswami (Journal of Molecular Histology, 2024)

Investigation of radioactivity and heavy metal levels in soil samples from neutral and vegetation land of Punjab, India - Sanjeet S. Kaintura; Swati Thakur; Sarabjot Kaur; Soni Devi; Katyayni Tiwari; Priyanka; Arzoo Sharma; Pushpendra P. Singh (Environmental Monitoring and Assessment, 2024)

Synthesis, Structural, Spectroscopic, Fluorescence, and Dielectric Studies of Bis-(4-Aminopyridine)-Zinc(II) Acetate: A Metal–Organic Crystal - Helen Merina Albert; R. Priya; Bajirao Bhila Ahire; N. S. M. P. Latha Devi; J. Madhuri Sailaja; S. Raziya Tabassum; Nellore Manoj Kumar; C. Alosious Gonsago (Journal of Fluorescence, 2024)

Proactive Approaches to cGMP Compliance: Insights and Key Takeaways from USFDA Warning Letters to Pharmaceutical Industries Between 2019 and 2024 - Gayatri Aglave; Sravani Yerram; Jayasri Devi Patnam; C. S. Ajmal; V. P. Muhammad Nizam; Ramesh Joga; Rajeev Singh Raghuvanshi; Saurabh Srivastava (Journal of Pharmaceutical Innovation, 2024)

Study of iron-based metal–organic framework for selenite removal from water - V. Sharma; P. Borah; S. S. Bhinder; S. K. Kansal; P. Devi (International Journal of Environmental Science and Technology, 2024)

Native bio-control agents from the rice fields of Telangana, India: characterization and unveiling the potential against stem rot and false smut diseases of rice - Sowmya Vanama; N. S. Raja Gopalan; Maruthi Pesari; M. Baskar; Uma Devi Gali; D. Ladha Lakshmi; P. Koteshwar; G. Jesudasu; Santosha Rathod; M. Srinivas Prasad; Rajanikanth Panuganti; R. M. Sundaram; et al. (World Journal of Microbiology and Biotechnology, 2024)

Antibiofilm potential of gallic acid against Klebsiella pneumoniae and Enterobacter hormaechei : in-vitro and in-silico analysis - Pooja P. Rajan; Praveen Kumar; Minsa Mini; Devi Jayakumar; Parvathi Vaikkathillam; Sneha Asha; Aparna Mohan; Manjusree S (Biofouling, 2023)

A comprehensive review on current trends and development of biomethane production from food waste: Circular economy and techno economic analysis - M. Keerthana Devi; S. Manikandan; P. Senthil Kumar; P.R. Yaashikaa; M. Oviyapriya; Gayathri Rangasamy (Fuel, 2023)

New Record of Champsodon Atridorsalis Ochiai & Nakamura, 1964 from the South Eastern Arabian Sea - Rekha Devi Chakraborty; G. Maheswarudu; P. T. Jinesh; N Ragesh; L Sreesanth; Josileen Jose; Pillai S Lakshmi; A P Dineshbabu; Rajendra Naik; T B Retheesh (Thalassas: An International Journal of Marine Sciences, 2023)

Influence of age, diurnal cycle, and plant and non-plant surfaces on oviposition by Spodoptera litura (Fabricius)(Lepidoptera: Noctuidae) - S. P. Yadav Deen; Anupam Varshney Sharma; Priya Singh; Satish Ganta; P. R. Ragesh; Smriti Sharma; Tarkeshwar; Kapinder; Jyotsna Singh; Mayanglambam Rojina Devi; Sanjiv Mullick (International Journal of Tropical Insect Science, 2023)

Sedimentary seagrass carbon stock and sources of organic carbon across contrasting seagrass meadows in Indonesia - Yusmiana P. Rahayu; Mariska A. Kusumaningtyas; August Daulat; Agustin Rustam; Devi D. Suryono; Hadiwijaya L. Salim; Restu N. A. Ati; Nasir Sudirman; Terry L. Kepel; Andreas A. Hutahaean; Novi S. Adi (Environmental Science and Pollution Research, 2023)
Seagrass meadows are an important component of coastal ecosystems globally, and they capture and store organic carbon in living biomass and sediments. Geographical estimates of blue carbon in seagrass habitats are regionally biased, with limited information from the Indo-Pacific region, including Indonesia. Seagrass extent in Indonesia is declining rapidly, and it has been suggested that marine protected areas (MPAs) are an important instrument to support protection of seagrass ecosystems and their services. Thus, this study is aimed at quantifying and comparing sedimentary carbon stocks and sources of organic carbon from seagrass meadows located in undisturbed areas outside MPA, disturbed areas outside MPA, and within MPA in three small islands in Indonesia. The sediment carbon stocks from this study ranged from 19.81 to 117.49 Mg C ha −1 , with the highest stock measured inside MPA (77.15 ± 1.38 Mg C ha −1 ), followed by undisturbed outside MPA (36.08 Mg C ha −1 ), and the lowest stock at disturbed outside MPA (21.86 ± 0.31 Mg C ha −1 ). The predominant source of organic carbon in disturbed meadows was from coastal POM (particulate organic matter, ~ 36%), while in MPA and undisturbed sites, the main source was from seagrass, with ~ 38% and ~ 60% contributions, respectively. The results of this study add more data and information on seagrass blue carbon potential from three different islands with different degrees of disturbance in Indonesia.

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

Genetic resources of sticky rice in India: status and prospects - Raj K. Gautam; Sapna Langyan; S. Vimla Devi; Rakesh Singh; D. P. Semwal; Sharik Ali; G. S. Mangat; Sutapa Sarkar; Torit Baran Bagchi; Somnath Roy; P. Senguttuvel; S. Bhuvaneswari; et al. (Genetic Resources and Crop Evolution, 2023)

Virgin Coconut Oil (VCO) Ameliorates High Fat Diet (HFD)-Induced Obesity, Dyslipidemia and Bestows Cardiovascular Protection in Rats - Shilpa S. Shetty; P. G. Roopashree; S. V. Ramesh; Ajeet Singh; M. Arivalagan; M. R. Manikantan; Ullal Harshini Devi; K. P. Sharmila; K. B. Hebbar; N. Suchetha Kumari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Non-thermal plasmas for disease control and abiotic stress management in plants - Susmita C.; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Eric Lichtfouse; Bhojaraj Naik; Ramya P.; Kalyani Kumari; Sanjay Kumar (Environmental Chemistry Letters, 2022)

Apomixis: A Foresight from Genetic Mechanisms to Molecular Perspectives - C. Susmita; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Dinesh K. Agarwal (The Botanical Review, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Unmanned Aerial Vehicle-Based Multispectral Remote Sensing for Commercially Important Aromatic Crops in India for Its Efficient Monitoring and Management - Sonam Bahuguna; Shubham Anchal; Deepak Guleria; Mamta Devi; Meenakshi; Devshree Kumar; Rakesh Kumar; P. V. S. Murthy; Amit Kumar (Journal of the Indian Society of Remote Sensing, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Biodegradation of low-density polyethylene and polypropylene by microbes isolated from Vaigai River, Madurai, India - K. Nanthini Devi; P. Raju; P. Santhanam; S. Dinesh Kumar; N. Krishnaveni; J. Roopavathy; P. Perumal (Archives of Microbiology, 2021)

Gibberellic acids promote growth and exopolysaccharide production in Tetraselmis suecica under reciprocal nitrogen concentration: an assessment on antioxidant properties and nutrient removal efficacy of immobilized iron-magnetic nanoparticles - A. Prathipa; G. Manigandan; S. Dinesh Kumar; P. Santhanam; P. Perumal; N. Krishnaveni; K. Nanthini Devi; S. Vijayalakshmi (Archives of Microbiology, 2021)

Trends of winter precipitation extremes over Northwest Himalaya - N. Narasimha Rao; Usha Devi; M. S. Shekhar; G. P. Singh (Hydrological Sciences Journal, 2021)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Correction of mesoscale model daily precipitation data over Northwestern Himalaya - Usha Devi; M. S. Shekhar; G. P. Singh (Theoretical and Applied Climatology, 2021)

Statistical Method of Forecasting of Seasonal Precipitation over the Northwest Himalayas: North Atlantic Oscillation as Precursor - Usha Devi; M. S. Shekhar; G. P. Singh; S. K. Dash (Pure and Applied Geophysics, 2020)

Novel formulations of Bacillus thuringiensis var. kurstaki: an eco-friendly approach for management of lepidopteran pests - P. S. Vimala Devi; P. Duraimurugan; K. S. V. Poorna Chandrika; V. Vineela; P. P. Hari (World Journal of Microbiology and Biotechnology, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Methodological application of quantile mapping to generate precipitation data over Northwest Himalaya - Usha Devi; Manorama S. Shekhar; Gyan P. Singh; Nalamasu N. Rao; Uma S. Bhatt (International Journal of Climatology, 2019)
Continuous high quality data are critical for weather and climate investigations. Numerous data gaps exist particularly over mountainous regions which limits the ability to construct climatologies and perform trend analysis. This study addresses the issue of sparse precipitation data over Northwest Himalaya (NWH) and fills data voids by applying the quantile mapping (QM) method. QM is applied to observed winter precipitation for a period of 25 years (1991–1992 to 2015–2016) to construct a continuous reliable data set. The first 20 years (1991–1992 to 2010–2011) are used for training and the remaining 5 years (2011–2012 to 2015–2016) are used for validation. In total, 10 stations are available for this study and each one is considered serially as a reference to generate daily precipitation values at the other stations. The mean precipitation of NWH region is constructed by considering the mean of all the stations. Standard statistical measures like root mean square errors, standard deviation, skill score and its decompositions are applied to evaluate the generated datasets. Based on statistical analysis, the Kanzalwan station, located in Great Himalaya range, is one of the best performing reference stations for generating precipitation values over NWH. The statistical measures of this station show the highest skill scores, lowest root mean square error and lowest standard mean errors for all winter months except January. This study provides a successful application of QM to generate precipitation data for climate analysis over the complex terrain of the Himalaya region.

Variability of Diurnal Temperature Range During Winter Over Western Himalaya: Range- and Altitude-Wise Study - M. S. Shekhar; Usha Devi; S. K. Dash; G. P. Singh; Amreek Singh (Pure and Applied Geophysics, 2018)

Synthesis, Photoluminescence Behavior of Green Light Emitting Tb(III) Complexes and Mechanistic Investigation of Energy Transfer Process - Manju Bala; Satish Kumar; Rekha Devi; Avni Khatkar; V. B. Taxak; Priti Boora; S. P. Khatkar (Journal of Fluorescence, 2018)

Relative Study of Luminescent Properties with Judd-Ofelt Characterization in Trivalent Europium Complexes Comprising ethyl-(4-fluorobenzoyl) Acetate - Rekha Devi; Sangeeta Chahar; S. P. Khatkar; V. B. Taxak; Priti Boora (Journal of Fluorescence, 2017)

Foraminifera of Lakshadweep Archipelago, Arabian Sea - Subhadra Devi Gadi; P. Vidya; M. S. Mustak; K. P. Rajashekhar (Proceedings of the Zoological Society, 2016)

Studies on Photocleavage, DNA Binding, Cytotoxicity, and Docking Studies of Ruthenium(II) Mixed Ligand Complexes - Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; N. Deepika; V. Ravi Kumar; P. Venkat Reddy; K Nagasuryaprasad; Surya S. Singh; Penumaka Nagababu; S. Satyanarayana (Journal of Fluorescence, 2016)

Expression and inheritance of chimeric cry2AX1 gene in transgenic cotton plants generated through somatic embryogenesis - A. R. Sakthi; A. Naveenkumar; P. S. Deepikha; N. Balakrishnan; K. K. Kumar; E. Kokila Devi; V. Balasubramani; L. Arul; P. K. Singh; D. Sudhakar; V. Udayasuriyan; P. Balasubramanian (In Vitro Cellular & Developmental Biology - Plant, 2015)

Electrical resistivity imaging over natural (in situ) geological samples using physical model studies - Rajesh Rekapalli; Padmavathi Devi P; V. S. Sarma; P. Rajendra Prasad (Arabian Journal of Geosciences, 2014)

Microsporogenesis and pollen formation in Zingiber officinale Roscoe - S. Subbarayudu; B. Shankar Naik; H. Sunitibala Devi; B. S. Bhau; P. Shaik Sha Valli Khan (Plant Systematics and Evolution, 2014)

Synthesis, Characterization, DNA Binding Studies, Photocleavage, Cytotoxicity and Docking Studies of Ruthenium(II) Light Switch Complexes - Nazar Mohammed Gabra; Bakheit Mustafa; Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; P. Venkat Reddy; Kotha Laxma Reddy; S. Satyanarayana (Journal of Fluorescence, 2014)

Assessment of coastal dune characteristics using georadar imaging and sedimentological analysis: Odisha and Visakhapatnam, India - K. Devi; M. C. Raicy; Deshraj Trivedi; P. Srinivasan; S. G. N. Murthy; Ronald J. Goble; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Fungal biodegradation of phthalate plasticizer in situ - S. Pradeep; P. Faseela; M. K. Sarath Josh; S. Balachandran; R. Sudha Devi; Sailas Benjamin (Biodegradation, 2013)

Integrated approach of assessing sedimentary characteristics of onshore sand deposits on the Velankanni coast, Tamil Nadu, India: sheds light on extreme wave event signatures - K. Devi; C. S. Vijaya Lakshmi; M. C. Raicy; P. Srinivasan; S. G. N. Murthy; S. M. Hussain; Ilya Buynevich; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Economic analysis of risk of gastrointestinal parasitic infection in cattle in North Eastern States of India - S. Bandyopadhyay; S. Mandal; K. K. Datta; P. Devi; S. De; A. K. Bera; D. Bhattacharya (Tropical Animal Health and Production, 2010)

Sarcoptic mange infestation in pigs in a hilly region of Meghalaya - M. Das; R. Laha; P. Devi; R. K. Bordoloi; S. Naskar (Tropical Animal Health and Production, 2010)

Multiplex PCR for identification of parasitic eggs of Oesophagostomum spp. Isolated from sheep and goat - S. Bandyopadhyay; S. Naskar; P. Devi; A. K. Bera; S. De; D. Pan; T. Rana; S. Das; S. Sikdar; D. Bhattacharya (Proceedings of the Zoological Society, 2009)

Evaluation of in vitro antimicrobial activity of leaf and stem essential oils of Chloroxylon swietenia DC. - S. Ravi Kiran; P. Sita Devi; K. Janardhan Reddy (World Journal of Microbiology and Biotechnology, 2008)

Characterization of Bacillus thuringiensis Strain DOR4 Toxic to Castor Semilooper Achaea janata: Proteolytic Processing and Binding of Toxins to Receptors - Madhusudhan Budatha; Gargi Meur; P. S. Vimala Devi; P. B. Kirti; Aparna Dutta-Gupta (Current Microbiology, 2008)

Identification of a high frequency of chromosomal rearrangements in the centromeric regions of prostate cancer patients - V. Balachandar; B. Lakshman Kumar; K. Sasikala; P. Manikantan; R. Sangeetha; S. Mohana Devi (Journal of Zhejiang University-SCIENCE B, 2007)

Effect ofVitex negundo leaf extract on the free radicals scavengers in complete Freund's adjuvant induced arthritic rats - P Renuka Devi; S Krishna Kumari; C Kokilavani (Indian Journal of Clinical Biochemistry, 2007)

Barley-based medium for the cost-effective production of Bacillus thuringiensis - P. S. Vimala Devi; T. Ravinder; C. Jaidev (World Journal of Microbiology and Biotechnology, 2005)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

Cholinesterase Activity in Clam Meretrix casta: Possible Biomarker for Organophosphate Pesticide Pollution - K. P. Devi; S. K. Pandian; N. S. S. Kumar (Bulletin of Environmental Contamination and Toxicology, 2005)

An efficient protocol for shoot regeneration and genetic transformation of pigeonpea [Cajanus cajan (L.) Millsp.] using leaf explants - S. Dayal; M. Lavanya; P. Devi; K. K. Sharma (Plant Cell Reports, 2003)

Plant regeneration from scutella of immature embryos of diverse sorghum genotypes - R. V. Sairam; N. Seetharama; T. Shyamala; P. S. Devi (Cereal Research Communications, 2000)

Culture and regeneration of mesophyll-derived protoplasts of sorghum [ Sorghum bicolor (L.) Moench] - R. V. Sairam; N. Seetharama; P. S. Devi; A. Verma; U. R. Murthy; I. Potrykus (Plant Cell Reports, 1999)

Microprojectile-mediated transient and integrative transformation of rice embryogenic suspension cells: effects of osmotic cell conditioning and of the physical configuration of plasmid DNA - Y. L. Nandadeva; C. G. Lupi; C. S. Meyer; P. S. Devi; I. Potrykus; R. Bilang (Plant Cell Reports, 1999)